A Rapid Review on Software Reuse in Digital Twin Development Lifecycle - Botelho, Lorena Mamede; Werner, Claudia; Farias, Claudio Miceli de (Anais do Workshop em Engenharia de Software para Gêmeos Digitais (SEDT); 2025: Anais do I Workshop em Engenharia de Software para Gêmeos DigitaisDO - 10.5753/sedt.2025.14763, 2025)
Digital Twin has become a trend in literature in the past decade. Despite its popularity, researchers reported the lack of standardized development approaches and general guidelines to foster its adoption. In this study, we conducted a rapid review to investigate whether, and under what conditions, Software Reuse techniques can address these challenges. Through a content analysis of twenty-two primary studies, results suggest that Software Reuse techniques contribute to reducing development time and enhancing composability in the Digital Twin construction process. Component-Based Software Engineering emerged as the predominant reuse approach among the analyzed studies. However, the review also identified a notable lack of empirical evaluation regarding the proposed reusable assets, limiting the evidence base for the reported benefits of Software Reuse in Digital Twin development.